Oceanographic habitat suitability is positively correlated with the body condition of a coastal‐pelagic fish. (21st October 2019) - Champion, Curtis; Hobday, Alistair J.; Pecl, Gretta T.; Tracey, Sean R.
Abstract: Species distribution models are commonly used to determine a species' probability of occurrence but have not been used to examine the effect of environmental habitat suitability on fish condition, which is considered to be an integrated measure of physiological status. Here, we test for a relationship between oceanographic habitat suitability and the body condition of kingfish ( Seriola lalandi ) from eastern Australia. We (a) test whether individuals sampled from areas of high‐quality habitat were in better condition than individuals sampled from areas of low‐quality habitat, and (b) assess whether the condition of kingfish responded to oceanographic habitat suitability predicted at varying time‐before‐capture periods. Kingfish habitat was modelled as a function of sea surface temperature, sea‐level anomaly and eddy kinetic energy in a generalized additive modelling framework. Model predictions were made over one‐ to six‐week time‐before‐capture periods and compared to field‐derived kingfish condition data measured using bioelectrical impedance analysis. Oceanographic habitat suitability was significantly correlated with kingfish condition at time‐before‐capture periods ranging from one to four weeks and became increasingly correlated at shorter lead‐times. Our results highlight that (a) fish condition can respond sensitively to environmental variability and this response can be detected using oceanographic habitat suitability models, and (b) climate change may drive extensions in species range limits through spatial shifts in oceanographic habitat quality that allow individuals to persist beyond historical range boundaries without their body condition being compromised.